Expanding the mutational spectrum of monogenic hypogonadotropic hypogonadism: novel mutations in ANOS1 and FGFR1 genes - Agnieszka Gach; Iwona Pinkier; Maria Szarras-Czapnik; Agata Sakowicz; Lucjusz Jakubowski (Reproductive Biology and Endocrinology, 2020)
Abstract Background Congenital hypogonadotropic hypogonadism (CHH) is a rare disease, triggered by defective GnRH secretion, that is usually diagnosed in late adolescence or early adulthood due to the lack of spontaneous pubertal development. To date more than 30 genes have been associated with CHH pathogenesis with X-linked recessive, autosomal dominant, autosomal recessive and oligogenic modes of inheritance. Defective sense of smell is present in about 50–60% of CHH patients and called Kallmann syndrome (KS), in contrast to patients with normal sense of smell referred to as normosmic CHH. ANOS1 and FGFR1 genes are all well established in the pathogenesis of CHH and have been extensively studied in many reported cohorts. Due to rarity and heterogenicity of the condition the mutational spectrum, even in classical CHH genes, have yet to be fully characterized. Methods To address this issue we screened for ANOS1 and FGFR1 variants in a cohort of 47 unrelated CHH subjects using targeted panel sequencing. All potentially pathogenic variants have been validated with Sanger sequencing. Results Sequencing revealed two ANOS1 and four FGFR1 mutations in six subjects, of which five are novel and one had been previously reported in CHH. Novel variants include a single base pair deletion c.313delT in exon 3 of ANOS1, three missense variants of FGFR1 predicted to result in the single amino acid substitutions c.331C > T (p.R111C), c.1964 T > C (p.L655P) and c.2167G > A (p.E723K) and a 15 bp deletion c.374_388delTGCCCGCAGACTCCG in exon 4 of FGFR1. Based on ACMG–AMP criteria reported variants were assigned to class 5, pathogenic or class 4, likely pathogenic. Protein structural predictions, the rarity of novel variants and amino acid conservation in case of missense substitutions all provide strong evidence that these mutations are highly likely to be deleterious. Conclusions Despite the fact that ANOS1 and FGFR1 are classical CHH genes and were thoroughly explored in several CHH cohorts we identified new, yet undescribed variants within their sequence. Our results support the genetic complexity of the disorder. The knowledge of the full genetic spectrum of CHH is increasingly important in order to be able to deliver the best personalised medical care to our patients.